A Narrative Review of the Usage of Creative Solutions to Enhance Disabled Patients' Quality of Life and Wellbeing by Occupational Therapists - Sarah Mohammed Alageel (Hindawi-Wiley, 2022)
Introduction. Occupational therapists play a crucial role in the rehabilitation process, as they maximise patients' independence and participation in meaningful occupations by adopting creative solutions in their treatment plan. Recognizing the importance of creative work and incorporating it into daily activities can be a powerful technique for enhancing quality of life. As a result, OTs must comprehend the significance of using creativity on a daily basis with patients. Creativity has been implicit in occupational therapists' values and practices since the occupational therapy field's early days. In particular, OTs use meaningful activities to promote health, wellbeing, and independence, which have traditionally had a strong connection with creativity. Primarily, the OT uses practical exercise to create wellbeing and autonomy, which have had a healthy linkage with imagination. The OT has used creative exercise as a treatment technique since the beginning of the profession. Method. In this paper, a Narrative Review Checklist was used to carry out specific checks of manuscripts' structures and a careful selection of the articles which are included in the manuscript. In addition, articles referenced in review articles or guidelines were reviewed for inclusion. Findings. This review has shown that the primary motivation for implementing creative activities was to improve the patient performance, wellbeing, and self-esteem. The goal of implementing creative activities was to assist the client in self-expression as well as experience joy and desire. As a result, the necessity to investigate the influence of creative solutions in treatment from an OT standpoint has been identified. Conclusion. Future studies should focus on how it is important to consider the patient's intrinsic and extrinsic motivations when designing creative solutions, as well as how the disability affects their daily activities, occupations, and adherence to a treatment plan.